Smalltracer: Um verificador de tipos e condições para Smalltalk - Meira, Silvio R. L.; Lisboa, Paulo H. C. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1992: Anais do VI Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1992.25184, 1992)
This paper discusses the difficulty of today's object oriented languages and programming environments to keep together some benefits of the paradigm, such as fast prototyping and linguistic unity in a rider range of stages of the software life cycle. A type and condition environment, Smalltracer is proposed here as a possible solution for some of the problems that occur in Smalltalk and in the Smalltalk/V environment.